Interculturality of the human right to peace in Mexico - Cantero-Ramírez, Margarita (2023)
This article reflects on the interculturality of the human right to peace in Mexico to recognize how the encounter between cultures is fostered where economic, cultural and social elements are exchanged, highlighting that conflicts can arise and derive in violence transgressing peace. The proposal of real law is described, which uses the intercultural method to consider the customary law of native peoples, their traditional principles, as well as their cosmovisions and build peaceful environments. Challenges, proposals and strategies involving native peoples were also identified to guarantee the right in question. Finally, it is invited to consider the legal, theoretical and practical elements presented to continue developing empirical approaches from the intercultural approach for peace that will allow the formation of critical and conscious subjects of cultural differences as an area of opportunity to guarantee the human right to peace.